WINE AND WINE TOURISM IN MACEDONIA - Soltirovska, Dragana (Journal of process management and new technologies, 2016)
Wine (Latin: vinum) is an alcoholic beverage obtained by the fermentation of the grapes, the fruit of the vine plant. In Europe, according to legal regulations, the wine is the product obtained exclusively by full or partial fermentation of fresh grapes, clove or not, or of grape must. The transformation of grapes into wine is called vinification. The science of wine is called oenology. In some other parts of the world, the word wine can be true of alcohol obtained from other types of fruit. These wines are referred to as fruit wines, or wear a name by which the fruit is used for obtaining them (for example apple wine). Wine tourism is a type of tourism that involves visiting wineries, tasting, consumption and purchase of wine, usually directly from the manufacturer. This type of tourism includes visits to wineries, vineyards and restaurants famous for special local wines, as well as organized wine tours, visits to wine festivals and other special events. Many wine regions around the world to promote this tourism because it affects very positively to the local economy. In these regions, viticulture and hospitality organizations have spent significant resources over the years for the promotion of wine tourism. Wine tourism in my country is respected, but strong growth.